Evaluasi dan Perbaikan Proses Bisnis Layanan Dataku Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: Layanan Dataku Dinas Komunikasi dan Informatika Kabupaten Sidoarjo) - Carellia An-nisa Monik; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Layanan Dataku is a service center for statistical data in the Communication and Information Agency of Sidoarjo Regency. Layanan Dataku has three business processes which are: data mining business process, data processing business process and data publication business process. In the service implementation, there are several stages that interfere with the business process. There are 7 potentials problems were considered with the highest RPN (Risk Priority Number) values which are when the Head of Service received a letter and gave a decision to extract data manually, the OPD gives a decision to permit data mining manually, the organization gives access to a limited data mining, the data processing section obtains data from third parties, prepares the data to be processed, gives a decision data publication feasibility, entering the website page. The first stage of this research is to identify the business processes, then to make a model of business processes using Business Process Model and Notation (BPMN), then conduct analysis and evaluation using the Failure Mode and Effect Analysis (FMEA) method to sort the problems based on the highest RPN values to be evaluated. The preparation of business process recommendations is improved by using the Business Process Improvement (BPI) method supported by Streamlining tools. There is an increase of 42.64% in data mining business processes, 31.99% in data processing and 0.18% in data publication. So that it can produce a faster duration of problem-solving and produce recommendations that can be applied to minimize problems that occur based on the results of evaluations that have been carried out.